Code Switching used by Indonesian EFL Teachers in Upper Secondary School - Hanifatul Husni; M. Affandi Arianto (Journal of English Language Teaching, 2023)
The purpose of this research was aimed to know the reasons why teacher use code-switching and know what types and functions of code-switching that used by teachers when teaching. The subject of this research was English teachers at MAN 4 Tanah Datar. This research was qualitative research. The data of this research were obtained from observation to find types and functions of code-switching and interview to find out the teachers’ reasons used code-switching. Then, the data was analyzed as descriptive qualitative research. The result of this research showed that the reasons why teachers used code-switching because it has a lot of positive effects to students understanding and can increase their grade. The most dominant types of code-switching that used by teachers is inter-sentential switching 32 times and the most dominant functions of code-switching used by teachers are repetitive function 31 times.